Dampak perubahan harga minyak dunia atas saham sektor transportasi dan logistik - Glory Benedicta Sumampouw; Mutiara Sweety Tudus (Riset Akuntansi dan Portofolio Investasi, 2023)
The issue of the global crisis in early 2023 is likely to have a certain impact on changes in world oil prices. As a result, this impact tends to become an issue that can affect stock price movements in the capital market. This study aims to determine the impact of oil prices on stock prices, especially in the transportation and logistics sector in the context of global crisis issues. The data used as a sample were obtained through observations from January 1 to April 30, 2023. This study finds that there is a tendency for the stock market price to decline in the transportation and logistics sector, even though world oil prices tended to be more stable. In addition, this study also finds that the stock market prices for the transportation and logistics sector tended to be more varied. Other findings show that the relationship between the share price of the transportation and logistics sector and world oil prices is insignificant even though it is weak and unidirectional.